Analysis Body Mass Index in COPD Patients at Pirngadi Regional General Hospital Medan - Siregar, Syahrianti Rizky Azzahra; Siregar, Julahir Hodmatua; Lubis, Marlina Elfa; Anshari, Zaim (PT Inovasi Pratama Internasional, 2025)
Chronic obstructive pulmonary disease (COPD) is a non-communicable disease (NCD) that is a global problem with high incidence, especially in developing countries. COPD is described as a respiratory disease with restricted airflow due to alveolar obstruction or lameness. This study aims to analyze the relationship between body mass index and the degree of COPD. The design of this study was cross-sectional. A total of 67 respondents were taken using the sample size formula. COPD patients at Pirngadi Hospital Medan, totaling 67 people, were taken as respondents in this study. Data collection was carried out using secondary data, namely medical records. The results of the research data were analyzed using the Spearman Test. The results showed that the degree of severe COPD was 25 respondents (37.3%). All respondents had a body mass index classified as underweight, namely 28 respondents (41.8). The correlation test of body mass index with COPD found a significant correlation between BMI and COPD degree -0.789 (p<0.05). Suggestions for further researchers could include other variables that may affect COPD, such as the effect of pharmacological and non-pharmacological therapies on the degree of COPD